Disclosure of Key Audit Matters in Banking Issuers for The Period 2022–2024 - Dejan Michael Parhusip; Nureni Wijayati (Eduvest - Journal of Universal Studies, 2026)
The implementation of Auditing Standard (SA) 701 on Communicating Key Audit Matters (KAM) represents a major development in auditor reporting—particularly within the banking industry, which is characterized by high regulatory intensity, operational complexity, and significant risk exposure. SA 701 requires auditors to disclose matters that required significant professional judgment during the audit, with the objective of enhancing transparency and increasing the informational value of the auditor’s report for stakeholders. This research aims to analyze KAM disclosures among Indonesian banking issuers during the 2022–2024 period and to identify challenges in implementing SA 701 at the public accounting firm (KAP) level. This descriptive qualitative case study analyzed 141 audited financial statements of banks listed on the Indonesia Stock Exchange, supported by semi-structured interviews with engagement partners from Big Four and Non–Big Four firms. KAM disclosures were classified into account-level and entity-level categories to identify patterns in determining significant audit areas. The results show that the average number of KAMs disclosed per auditor’s report is 1.32, consisting of 1.07 account-level KAMs and 0.26 entity-level KAMs. Allowance for Expected Credit Losses (ECL/CKPN) is the most frequently disclosed KAM, appearing in all observations, followed by issues related to financial reporting information systems. These findings indicate that credit risk assessment and IT system reliability remain the primary audit focus in the banking sector. While SA 701 does not substantially alter audit procedures, it increases documentation, coordination, and review requirements.